The Effectiveness of PRP on Reducing Blood Glucose Levels in Diabetic Mice - Yuliandari, Aisyara; Hartuti, Yeli; Tomahu, Dea Yuni Putri; Hartini H (Jurnal Analis Laboratorium Medik, 2022)
PRP contains growth factors that have the potential to repair tissue damage, such as pancreatic damage in diabetes mellitus. Pancreas damage in diabetes mellitus is characterized by hyperglycemia. This study aimed to determine the effectiveness of PRP in reducing blood glucose levels in diabetic mice. Male Swiss Webster mice divided into 5 groups (normal group, DM group, PRP1 group, PRP2 group and PRP3 group). The DM, PRP1, PRP2 and PRP3 groups were given streptozotocin 45 mg/kgBW to induce diabetes mellitus. Mice in the PRP1, PRP2, and PRP3 groups that have indicated diabetes mellitus with glucose levels > 200 mg/dL will be given PRP with a dose of 0.1 mL; 0.3 mL; 0.5 mL intraperitoneally for 4 weeks. Data on blood glucose levels were analyzed using one-way ANOVA test and LSD test. The use of PRP in various doses, namely 0.1 mL, 0.3 mL, 0.5 mL, can reduce blood glucose levels in the PRP1 group (195.8 ± 14.04 mg/dl), PRP2 group(176.6 ± 9.37 mg/dl), PRP3 group (121 ± 5.52 mg/dl) compared to the DM group (392.6 ± 18.09 mg/dl). Dose of PRP of 0.5 mL gave a better effect on pancreatic tissue repair than the PRP1 and PRP2 groups, which were characterized by glucose levels that were close to the normal group (106.8 ± 10.61 mg/dl). Based on the results of the study, PRP 0.5 mL is effective in repairing pancreatic tissue which is characterized by a decrease in blood glucose levels in diabetic mice.